A 12-month clinical evaluation of pit-and-fissure sealants placed with and without etch-and-rinse and self-etch adhesive systems in newly-erupted teeth - Maryam Karami Nogourani; Mohsen Janghorbani; Parvin Khadem; Zahra Jadidi; Shahriar Jalali (University of São Paulo, 2012)
OBJECTIVES: The objective of this one-year clinical study was to investigate the effect of two adhesive systems (Adper Single Bond, a two-step etch-and-rinse and Clearfil SE Bond, a two-step self-etch system) on pit-and-fissure sealant retention in newly-erupted teeth. This study compared the success of the sealants in mesial and distopalatal grooves with and without these two adhesive systems. MATERIAL AND METHODS: In a clinical trial, 35 children aged 6-8 years undergoing sealant placement were recruited. This one-year clinical study scored 70 mesial and 70 distopalatal sealants of newly-erupted permanent maxillary first molar, with a split-mouth design. All children received sealant alone in one permanent maxillary molar tooth. Children were randomized into two groups. One group received Self-etch (Se) bond plus sealant and the other group received Single Bond plus sealant in another permanent maxillary molar tooth. Clinical evaluation at 3, 6 and 12 months was performed and the retention was studied in terms of the success and failure. RESULTS: The success rate of sealant in the distopalatal groove, using SeB at 3, 6 and 12 months was 93.3% (95% CI: 68.0, 99.8), 73.3% (95% CI: 44.9, 92.2) and 66.7% (95% CI: 38.4, 88.2), respectively. It was greater than that of the distopalatal groove in SB group with a success rate of 62.5% (95% CI: 35.4, 84.8), 31.3% (95% CI: 11.8, 58.7) and 31.3% (95% CI: 11.8, 58.7), at the three evaluation periods. The success rate of sealant in the mesial groove using SeB was 86.6% (95% CI: 59.5, 98.3), 53.3% (95% CI: 26.6, 78.7) and 53.3% (95% CI: 26.6, 78.7), while this was 100% (95% CI: 79.4, 100.0), 81.3% (95% CI: 54.4, 96.0) and 81.3% (95% CI: 54.4, 96.0) using SB, at 3, 6 and 12-month evaluation periods. CONCLUSIONS: These results support the use of these two bonding agents in pit-and-fissure sealants under both isolated and contaminated conditions. Further, Se bond seemed to be less sensitive to moisture contamination.